Let
![y=a(x-h)^2](https://img.qammunity.org/2023/formulas/mathematics/college/q15wsnp4mdhykynpocdgpht98n8zg0fbfo.png)
be the quadratic function that passes through the points (6,-3) and (3,0), then we get that:
![\begin{gathered} -3=a(6-h)^2, \\ 0=a(3-h)\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5ic2hry22yv82ozteaaltoeghb168fwana.png)
Now, notice that a≠0 because y=a(x-h)² is a quadratic equation, therefore, from the last equation we get:
![3-h=0.](https://img.qammunity.org/2023/formulas/mathematics/college/e3hct7u2rk6n3myytpq9qj1suyb996v5dg.png)
Adding h to the above equation we get:
![\begin{gathered} 3-h+h=0+h, \\ 3=h\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fp39owe9opypek67voqjj4hsp3stuusuvd.png)
Substituting h=3 in -3=a(6-h)² we get:
![-3=a(6-3)^2\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/yh38io8f1tsx3mmyr1fpluhor63w5anaea.png)
Simplifying the above equation we get:
![\begin{gathered} -3=a(3)^2, \\ -3=9a\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ko7a19renk65pgtr1699mnhnk0octnzdt6.png)
Dividing the above equation by 9 we get:
![\begin{gathered} -(3)/(9)=(9a)/(9), \\ -(1)/(3)=a\text{.} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wd7dtjygz73sgsl3t1teekwho2o4ukdjl0.png)
Answer:
![y=-(1)/(3)(x-3)^2\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/ky15b9zqwx1aj478k86t3q0rwfuvvsh7rw.png)